Transformasi Pendakwah Menjadi Microcelebrity: Studi Kasus Gus Kautsar Ploso Kediri di Media Sosial - Rofii Mashudi; Khalimatu Nisa (Muttaqien, 2025)
This research examines the transformation of Gus Kautsar Ploso Kediri from a traditional preacher to a microcelebrity figure through social media. Using qualitative methods and a case study approach, this study analyzes the transformation process, preaching strategies, and the impact of social media on preaching patterns and community acceptance. The main findings show that Gus Kautsar's popularity is not built through deliberate branding but results from the community's appreciation of the values of the da'wah he conveys. His relaxed, relevant, and spiritual delivery style makes him a respected role model. In addition, the role of the media team of Pondok Pesantren Al-Falah Ploso Kediri is very significant in documenting and publicizing his lectures. The community's support, which actively shares the content on various social media platforms, also expands the reach of Gus Kautsar's preaching. This phenomenon confirms that microcelebrity in the context of da'wah can form organically, supported by sincerity and dedication in conveying religious teachings. This research provides new insights into how social media can help the transformation of da'wah in the digital age while highlighting the importance of maintaining the authenticity and essence of religious messages amid the demands of social media.